The financial system in Mozambique: opportunities, barriers and market potential - Ferreira, Dora Patrícia Gameiro (2016)
This research is empirical and exploratory intending to analyse the attractiveness of banking in Mozambique, considering its positive outlook. To identify the opportunities and barriers, the methods adopted were elite interviews with banking executives, complemented by secondary data. The opportunities for new entrants seem to include bankarization and the emergence of micro and smallmedium enterprises; other avenues seem to include investment banking, support of mega-projects (e.g. energy, infrastructures) through syndicates and cooperation with multilaterals, and the participation in developing capital markets. Conversely, the main barriers include shortage of talent, inadequate infrastructures, poverty, unsophisticated entrepreneurial culture (e.g. informal economy, inadequate financial reporting), burdensome bureaucracy (e.g. visas), foreign exchange regulation, as well as low liquidity and high funding costs for banks. The key conclusions suggest a window of opportunity for niche markets, and new products and services in retail and investment banking.